Advanced basal cell carcinoma treated with vismodegib: impact on the lives of patients and their families. (1st December 2020) - Villani, A.; Cappello, M.; Costa, C.; Fabbrocini, G.; Scalvenzi, M.
Summary: Locally advanced basal cell carcinoma (laBCC) represented an uncommon, difficult‐to‐treat form of skin cancer until the recent approval of the Hedgehog inhibitor vismodegib. Approximately 80% of laBCCs occur in the head and neck region, causing disfiguring skin changes that have an impact on patient quality of life (QoL). Because the lives of patients with advanced BCCs are severely disrupted, it would be expected that the QoL family members involved in caregiving would also be affected. The aim of our study was to quantify the QoL of both patients and family members during vismodegib treatment using the Dermatology Life Quality Index and the Family Dermatology Life Quality Index, respectively.